Tinea Pedis Epidemiology and Importance from the Lens of Homelessness and Low-Resource Settings - Henderson, Armen; Rasul, Taha; Morgan, Orly; Rafie, Christine; Anderson, Jackson; Mathew, Megan; Bergholz, Daniel (Archives of Clinical and Biomedical Research, 2024)
Background: Tinea pedis is sometimes described as a penalty of civilization due to its propensity to spread in close-contact environments such as urban areas. Medically vulnerable urban populations, such as patients experiencing homelessness in cities, are at high risk for developing such infections. This paper reviews tinea pedis infections in homeless patients across multiple regions and explores management in low-resource settings. Methods: We conducted a literature search to characterize tinea pedis in homeless individuals across many geographic locations and offer recommendations for treatment in low-resource settings. A total of 60 PubMed articles were found using inclusion criteria containing terms ‘tinea pedis’ and ‘homeless’. Cohort studies, cross-sectional studies, and case-control studies published from 1979-2022 were evaluated. Results: In North America, the prevalence of tinea pedis among sheltered homeless individuals ranged from 3.2% to 13.5% compared to a frequency in the general population of approximately 10%. European studies showed a tinea pedis frequency of 4.4−34.9% in the general population and 3.2% in a homeless patient cohort. Our findings show that there is a statistically significant difference in disease burden and healthcare utilization between sheltered and unsheltered homeless patients. Findings from a medical student-run mobile clinic that provided supplies for the prevention and treatment of tinea pedis were also noted. Conclusion: Tinea pedis remains a ubiquitous disease among homeless patients across multiple geographic locations. Treatment in low-resource settings with simple interventions, such as antifungal powder, socks, and hygiene supplies, can potentially prevent tinea pedis outbreaks and improve disease burden in the PEH population.